Exploring faculty profile and technology transfer initiatives of a newly-instated state university in the Philippines - Dio, Ryan V.; Solano, Sheryl S.; Gonzales, Ivy Rose B.; Guarte, Hysa Brigitte D. (Institute of Advanced Engineering and Science, 2024)
The current university standards of research productivity focus on commercially adopted innovations in various industries. However, as a newly instated university in the Philippines, the Sorsogon State University’s research outputs in various disciplines are still lacking the necessary technology readiness level (TRL) that the industry requires. This descriptive method of research using correlation design utilized archival sources to determine the association between the faculty profile and the TRL of research outputs of the university. It was found that more than half of the 194 regular faculty members are specializing in soft sciences which resulted in the dominance of the basic type of research (250 out of 296) conducted from 2015 to 2020. Using the nine-point National Aeronautics and Space Administration (NASA) scale, the study revealed the right-skewed distribution of TRL assessment of faculty research outputs by area of specialization, almost all reaching TRL 1-4 and were not transferred to the intended beneficiaries. Factors such as academic rank, area of expertise, and highest educational attainment of faculty members were significantly associated with the TRL of their research outputs. Faculty members with the appropriate expertise and education preparation may be given the opportunity to collaborate with potential industry partners as part of the re-engineering process of the university’s research function.